Sentiment Analysis of Public on The COVID-19 (Corona Virus Disease 2019) Vaccination Moderna and Sinovac Vaccine Using Naïve Bayes - Salsyabila Vidia Nur Afni; Esi Putri Silmina (SENATIK STT Adisutjipto, 2022)
One of the government's attempts to break the COVID-19 (Corona Virus Disease 2019) chain was vaccination. Achieving the herd imunity is the main goal of vaccinating to control the COVID-19 pandemic. The Sinovac Vaccine and the Moderna Vaccine are examples of a type of inactivation vaccine. Indonesia's role in expressing and responding to the controversy often leads to public services used as materials to analyze who produced the data in support of the decision to compare the Sinovac type vaccine with the Moderna type vaccine. The purpose of the study is to see how people respond to vaccination with the various kinds of vaccines such as those taken in the study, the Moderna Vaccine type and the Sinovac Vaccine and the perceived value of sentiment analysis on the two vaccines. The method used in the study using the Naive Bayes Classification Method. The results from the study indicate that the Twitter users’sThe results from the study indicate that the Twitter users' twitter Sentiments Analysis with a positive testing of the Sinovac is larger than the Moderna Vaccine, which is 367 for the Sinovac Vaccine and 144 for the Moderna Vaccine.